If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B + -1(2) = -11 Multiply -1 * 2 B + -2 = -11 Reorder the terms: -2 + B = -11 Solving -2 + B = -11 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + B = -11 + 2 Combine like terms: -2 + 2 = 0 0 + B = -11 + 2 B = -11 + 2 Combine like terms: -11 + 2 = -9 B = -9 Simplifying B = -9
| 14-4y=y+x | | 1n+3-1=8 | | y-34=41/11(20-6) | | 3x-24=2x+26 | | y-34=41/11(18-6) | | 14x^2+9x=-1 | | -4+6(x-4)=15x+2-9x | | y-4/3-7=.25 | | 6n+3(n+2)=-(2n+7)+n | | -6m=42 | | 5x(2x+7)=2 | | 14x-8=34 | | 6-y/(-1)=0 | | 11-(3v+5)=3v-6 | | .15x=23 | | 3w+6-w=5w-2(w-3) | | 7y-4=216-2x | | 15-3.2x=-6.8 | | 8x+15=-57 | | (m+1.5)=1.5(2m+3) | | y=-x^2+8x-19 | | x+6(x-50)=750 | | 3y+2(y-5)=-1(3y-35)-y | | .55+q=.66 | | 5x-(2x+7)=2 | | -2(n+2)+6=16 | | .16x-.6=-.42 | | A-0.13=-.58 | | x+-4x=18 | | n+(n+2)=24-4(n+4) | | 16r-23=6r | | C=25000+40x+x^2 |